2019
DOI: 10.1111/jocn.14920
|View full text |Cite
|
Sign up to set email alerts
|

Parents' and nurses' experiences of partnership in neonatal intensive care units: A qualitative review and meta‐synthesis

Abstract: Aims and objectives:To explore how parents and nurses experience partnership in neonatal intensive care units and to identify existing barriers and facilitators to a successful partnership.Background: Family-centred care is recommended as a frame of reference for treatment and care in neonatal intensive care units. A key element in family-centred care is partnership. Such partnerships are characterised by complex interpersonal relationships and interactions between nurses and parents/families. Partnerships the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 56 publications
3
98
1
3
Order By: Relevance
“…Todos os incidentes críticos descritos demonstram a importância dos pais estarem inseridos no processo de cuidado, pois seu envolvimento pode trazer contribuições importantes para a segurança no cuidado com o bebê, e auxiliar na detecção e prevenção de eventos adversos ou quase falhas que não são percebidos ou notificados pela equipe assistencial 5,8,24 . Quando os pais estão inseridos nos cuidados, eles se sentem parte deste cuidado, e assim podem ser considerados pilares na segurança do paciente 9,25 . Portanto, o enfermeiro da Unidade Neonatal necessita desenvolver ações que auxiliem os profissionais a incentivarem os pais para este envolvimento, pois a inserção da família dentro do cuidado ainda gera muitos desafios à equipe de enfermagem.…”
Section: Discussionunclassified
“…Todos os incidentes críticos descritos demonstram a importância dos pais estarem inseridos no processo de cuidado, pois seu envolvimento pode trazer contribuições importantes para a segurança no cuidado com o bebê, e auxiliar na detecção e prevenção de eventos adversos ou quase falhas que não são percebidos ou notificados pela equipe assistencial 5,8,24 . Quando os pais estão inseridos nos cuidados, eles se sentem parte deste cuidado, e assim podem ser considerados pilares na segurança do paciente 9,25 . Portanto, o enfermeiro da Unidade Neonatal necessita desenvolver ações que auxiliem os profissionais a incentivarem os pais para este envolvimento, pois a inserção da família dentro do cuidado ainda gera muitos desafios à equipe de enfermagem.…”
Section: Discussionunclassified
“…These early interventions can help mothers develop the capability to cope with the traumatic shock and psychological distress of premature birth and NICU hospitalization and develop a rapport with the medical staff. A strategy in which the NICU nurses continue to communicate with the parents as equal partners in infant care and discuss their roles in achieving common goals can increase the sense of parenting efficacy and control over infant care (Brødsgaard et al, 2019 ). Our participants also mentioned that not only basic medical information about premature infants (such as weight gain, urine count, and test results) but also in-depth information (such as habitual positions when sleeping and unique characteristics like crying) helps parents feel close to their infants despite their physical separation.…”
Section: Discussionmentioning
confidence: 99%
“…While nurses are in the best position to reduce the barriers that hinder their partnership with the family, a key component of family-centred care (Brødsgaard et al, 2019 ), institutional limitations, such as inadequate time and lack of privacy, hinder opportunities to develop this partnership. The participants in this study identified the need for improved NICU systems and policies in healthcare institutions; they saw the lack of specialized staff and systematic training courses as challenges for quality care in supporting the maternal postpartum bonding process.…”
Section: Discussionmentioning
confidence: 99%
“…During EDP, the relationship between the EDP‐nurse and the family evolves, as the family gets even more independent and the EDP‐nurse takes on an increasingly consultative role while both parties strives towards the common goal of a normal everyday life. The mutual negotiation and pursuit of this common goal makes this relationship a partnership as defined by Reis and Brødsgaard (Brødsgaard et al, ; Reis et al, ) and not merely a family depending on a healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
“…FCC is defined as an approach to care based on four key principles: (a) dignity and respect, (b) shared responsibility, (c) knowledge sharing, and (d) partnership in care (Brødsgaard et al, ; IPFCC, ; Mikkelsen & Frederiksen, ). According to Reis, Rempel, Scott, Brady‐Fryer, and Van Aerde (, p. 677): “a partnership exists when there is a relationship between two or more people that have a shared goal.” A new qualitative review and meta‐synthesis of partnership concluded a successful partnership between parents’ and nurses’ can be achieved through co‐creation of mutual knowledge and development of competencies and negotiation of roles (Brødsgaard, Pedersen, Larsen, & Weis, ).…”
Section: Introductionmentioning
confidence: 99%